2005
DOI: 10.1007/s00441-005-0006-2
|View full text |Cite
|
Sign up to set email alerts
|

Stress hormone and male reproductive function

Abstract: The Leydig cell is the primary source of testosterone in males. Levels of testosterone in circulation are determined by the steroidogenic capacities of individual Leydig cells and the total numbers of Leydig cells per testis. Stress-induced increases in serum glucocorticoid concentrations inhibit testosterone-biosynthetic enzyme activity, leading to decreased rates of testosterone secretion. It is unclear, however, whether the excessive glucocorticoid stimulation also affects total Leydig cell numbers through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
189
1
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(204 citation statements)
references
References 49 publications
6
189
1
8
Order By: Relevance
“…This may be mediated by non-genomic mechanisms [Dong et al 2004] or genetic mechanisms through the inhibition of genes encoding testosterone biosynthetic enzymes [Payne and Sha 1991], such as 3b-hydroxysteroid dehydrogenase and 17a-hydroxylase/17-20-lyase [Hales and Payne 1989;Orr et al 1994]. Corticosterone also induces Leydig cell apoptosis [Chen et al 2012], resulting in a significant reduction in the secretion of testosterone [Hardy et al 2005] as confirmed by TUNEL. It appears that the number of apoptotic Leydig cells observed were not sufficient to cause a decrease in the level of testosterone after acute stress induction.…”
Section: Discussionmentioning
confidence: 99%
“…This may be mediated by non-genomic mechanisms [Dong et al 2004] or genetic mechanisms through the inhibition of genes encoding testosterone biosynthetic enzymes [Payne and Sha 1991], such as 3b-hydroxysteroid dehydrogenase and 17a-hydroxylase/17-20-lyase [Hales and Payne 1989;Orr et al 1994]. Corticosterone also induces Leydig cell apoptosis [Chen et al 2012], resulting in a significant reduction in the secretion of testosterone [Hardy et al 2005] as confirmed by TUNEL. It appears that the number of apoptotic Leydig cells observed were not sufficient to cause a decrease in the level of testosterone after acute stress induction.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the process of Leydig cell ageing, stress inhibits steroidogenic enzyme expression, subsequently decreasing testosterone secretion. 6,7,9 Lipofuscin is an undegradable polymorphous waste material that accumulates in the lysosomal compartment of post-mitotic and slowly dividing cells; importantly, lipofuscin levels progressively increase with age. For this reason, the change in the amount of lipofuscin within the senescenct cells is considered as a marker of cellular ageing.…”
Section: Introductionmentioning
confidence: 99%
“…In Leydig cells, prolonged exposure to high glucocorticoid concentrations during stress response directly inhibits the transcription of genes encoding enzymes involved in the synthesis of testosterone [60] as 3β-hydroxysteroid dehydrogenase (3β-HSD) and 17α-hydroxylase/17-20 lyase [61][62][63]. In addition, glucocorticoids cause apoptosis in Leydig cells [56], thus contributing to the reduction in testosterone secretion [3] observed during stress. It has been proposed that the activation of apoptosis in these cells may be related to the activation of the Fas system of procaspase 3 with the loss of mitochondrial membrane potential and the increase in the generation of ROS [3].…”
Section: Effect Of Glucocorticoids On Testicular Cellsmentioning
confidence: 99%
“…In addition, glucocorticoids cause apoptosis in Leydig cells [56], thus contributing to the reduction in testosterone secretion [3] observed during stress. It has been proposed that the activation of apoptosis in these cells may be related to the activation of the Fas system of procaspase 3 with the loss of mitochondrial membrane potential and the increase in the generation of ROS [3]. As mentioned above, the increase in glucocorticoid concentration may be related to the activation of apoptosis in testicular cells through an increase in ROS generation [48].…”
Section: Effect Of Glucocorticoids On Testicular Cellsmentioning
confidence: 99%
See 1 more Smart Citation